Modular multilevel inverter for renewable energy applications - Arikesh A.; A. K. Parvathy (Institute of Advanced Engineering and Science, 2020)
This paper proposes a Multilevel Inverter (MLI) which focuses on two objective , minimal voltage sources and lesser switching component. The proposed Asymmetrical Cascaded Multilevel Inverter (ACMLI) is able to achieve the objective by selectively opting the voltage level of DC sources chosen and implementing the mathematical operation of addition and subtraction on the DC sources. This system also utilizes multiple carrier sinusoidal pulse width modulation technique (MCS-PWM) for operating the switches. It is found that the number of switches required for proposed modular bridge ACMLI and modified H bridge ACMLI was lesser than the traditional Cascaded H bridge Multilevel Inverter (CHB-MLI). It is also evident that the number of DC voltage sources and filter required for smoothing the output waveform is reduced compared to the traditional MLI. The Total Harmonic Distortion (THD) for the proposed circuit was simulated and analyzed in MATLAB Simulink environment and the results are found to be very less and satisfactory. The proposed circuit can find its application in integrating Renewable Energy Sources (RES) to the utility grid, Electrical Vehicle (EV) , harmonic reduction and so on. The simulation results of the proposed circuits are tabulated and compared with the traditional cascaded MLI.